Multiple TLRs elicit alternative NLRP3 inflammasome activation in primary human monocytes independent of RIPK1 kinase activity - Unterberger, Sarah; Mullen, Lisa; Flint, Melanie S.; Sacre, Sandra (Frontiers in Immunology, 2023)
The canonical NOD-like receptor family pyrin domain containing 3 (NLRP3) pathway involves a priming step to induce pro-IL-1β followed by a secondary signal such as K+ efflux to activate inflammasome formation. This then leads to the maturation of IL-1β and the formation of gasdermin D (GSDMD) pores that initiate pyroptosis and mediate IL-1β release. In contrast, primary human monocytes also engage an alternative pathway in response to toll-like receptor (TLR) 4 activation, without the need for a secondary signal. Data from a monocyte-like cell line suggest that the alternative pathway functions via the TLR adaptor protein TIR-domain-containing adapter-inducing interferon-β (TRIF), receptor-interacting protein kinase 1 (RIPK1), FAS-associated death domain (FADD) and caspase-8 upstream of NLRP3 activation, but in the absence of K+ efflux or pyroptosis. Usage of the alternative pathway by other members of the TLR family that induce IL-1β but do not signal through TRIF, has yet to be explored in primary human monocytes. Furthermore, the mechanism by which IL-1β is released from monocytes remains unclear. Therefore, this study investigated if the alternative NLRP3 inflammasome pathway is initiated following activation of TLRs other than TLR4, and if GSDMD was necessary for the release of IL-1β. Monocytes were stimulated with ligands that activate TLR1/2, TLR2/6, TLR4 and TLR7 and/or TLR8 (using a dual ligand). Similar to TLR4, all of the TLRs investigated induced IL-1β release in a NLRP3 and caspase-1 dependent manner, indicating that TRIF may not be an essential upstream component of the alternative pathway. Furthermore, inhibition of RIPK1 kinase activity had no effect on IL-1β release. Although IL-1β was released independently of K+ efflux and pyroptosis, it was significantly reduced by an inhibitor of GSDMD. Therefore, it is feasible that low level GSDMD pore formation may facilitate the release of IL-1β from the cell, but not be present in sufficient quantities to initiate pyroptosis. Together these data suggest that the alternative pathway operates independently of RIPK1 kinase activity, downstream of diverse TLRs including TLR4 in primary human monocytes and supports the potential for IL-1β release via GSDMD pores alongside other unconventional secretory pathways.